Analisis Pengaruh Pelayanan Terhadap Kepuasan Penumpang di Area Drop Zone dan Pick Up Zone Bandar Udara Internasional Lombok ( Nusa Tenggara Barat ) - Marisa Novani; Djoko Widadgo (Jurnal Multidisiplin Madani, 2022)
This study aims (1) to determine whether there is an effect of service on passenger satisfaction in the drop zone and pick up zone area of Lombok International Airport (2) to find out how much influence the service has on passenger satisfaction in the drop zone and pick up zone area of the International Airport. Lombok. This study uses quantitative methods with data collection techniques using questionnaires and observation. The population in this study were passengers in the drop zone and pick-up zone area of Lombok International Airport, the number of which was not counted by taking a sample of 100 respondents. The results showed that the t-count value was 20.694 with a significance level of 0.000 <0.05. Which means that service has a positive and significant effect on passenger satisfaction in the drop zone and pick up zone areas. The passenger satisfaction variable is obtained from the R Square value, which is 0.814 or 81.4%. This means that the passenger satisfaction variable (Y) is influenced by the service variable (X) of 81.4% and the remaining 18.6% is influenced by other variables outside the variables in this study.